Stabilization, Syndication, and Pricing of IPOs - Chowdhry, Bhagwan; Nanda, Vikram (Journal of Financial and Quantitative Analysis, 1996)
We argue that in the after-market trading of an IPO, the underwriting syndicate, by standing ready to buy back shares at the offer price ("price stabilization"), compensates uninformed investors ex post for the adverse selection cost they face in bidding for IPOs. This domi? nates ex ante compensation by underpricing. The reason is that stabilization exploits ex post information about investor demand whereas underpricing must be based on ex ante infor? mation. However, liquidity and syndication costs constrain the use of stabilization which, in equilibrium, generates some underpricing as well. We develop a model that formalizes this intuition and generates several empirical implicatio